Салон красоты. Наперегонки с судьбой: [роман] / М. Ветрова - Ветрова Мария (Русский романс, 2002)
Экземпляры: (20181011) / Инвентарный номер: 28294 / Цена: / Сис.шифр: Р2 / Авт.знак: В 39 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6